High technology and economic development : the BioCity Nottingham technology incubator - Ehret, Michael, (SAGE Knowledge. Cases., 2017)
Since the 1990s, public policy makers and private investors have been creating bio-incubators with the aim of obtaining a foothold in what many presume is one of the hottest future industries. This case study provides an in-depth picture of the biggest UK-based bio-incubator BioCity Nottingham. The study outlines the history and regional context of the incubator as well as its service portfolio and a profile of its supported firms. The study provides insights into the formation of biotechnology companies, the role of the regional context in shaping business models and the emergence of a science-based business network. As a major implication, Nottingham's location, remote from the epicentre of both science and venture capital in the UK, favours service-based business models. BioCity provides a fascinating opportunity to become acquainted with local conditions of business incubation.